Enhanced the Optical Power of AlGaN-Based Deep Ultraviolet Light-Emitting Diode by Optimizing Mesa Sidewall Angle - Qian Chen; Huixue Zhang; Jiangnan Dai; Shuang Zhang; Shuai Wang; Ju He; Renli Liang; Zi-Hui Zhang; Changqing Chen (IEEE Photonics Journal, 2018)
In this work, we propose and optimize the sidewalls for the mesa to enhance the optical power for AlGaN-based deep ultraviolet light-emitting diodes (LEDs). We obtain the mesa with the inclined sidewalls by conducting dry etching. The optical performance for LED devices with different inclination angles are tested by putting the integrated sphere on the sapphire side of the devices. The DUV LED with the optimal angle of 37.83° yields the 48% optical power enhancement at the current density of 35 A/cm2 as compared with the reference device. The physical mechanism for the impact of the mesa inclination angle on the light extraction efficiency is also discussed both theoretically and experimentally. Then, we find that once the Al reflector is evaporated on the insulated silica dioxide that is coated on the sidewall of the mesa, the light extraction efficiency for the TM-polarized DUV photons and the optical power can be further improved.